Current practice and short-term outcomes of therapeutic mammaplasty in the international TeaM multicentre prospective cohort study. Issue 13 (22nd August 2018) - O'Connell, R L; Baker, E; Trickey, A; Rattay, T; Whisker, L; Macmillan, R D; Potter, S; Achuthan, R; Aggarwal, S; Baker, E; Basu, N; Brock, L; et al.
Abstract: Background: Therapeutic mammaplasty, which combines breast reduction and mastopexy techniques with tumour excision, may extend the boundaries of breast-conserving surgery and improve outcomes for patients, but current practice is unknown and high-quality outcome data are lacking. This prospective multicentre cohort study aimed to explore the practice and short-term outcomes of the technique. Methods: Consecutive patients undergoing therapeutic mammaplasty at participating centres between 1 September 2016 and 30 June 2017 were recruited to the study. Demographic, preoperative, operative, oncological and complication data were collected. The primary outcome was unplanned reoperation for complications within 30 days of surgery. Secondary outcomes included re-excision rates and time to adjuvant therapy. Results: Overall, 880 patients underwent 899 therapeutic mammaplasty procedures at 50 centres. The most common indications were avoidance of poor cosmetic outcomes associated with standard breast-conserving surgery (702 procedures, 78·1 per cent) or avoidance of mastectomy (379, 42·2 per cent). Wise-pattern skin incisions were the most common (429 of 899, 47·7 per cent), but a range of incisions and nipple–areola pedicles were used. Immediate contralateral symmetrization was performed in one-third of cases (284 of 880, 32·3 per cent). In total, 205 patients (23·3 per cent) developed a complication, but only 25 (2·8 per cent) required reoperation. Median postoperative lesion size was 24·5 (i.q.r. 16–38) mm. Incomplete excision was seen in 132 procedures (14·7 per cent), but completion mastectomy was required for only 51 lesions (5·7 per cent). Median time to adjuvant therapy was 54 (i.q.r. 42–66) days. Conclusion: Therapeutic mammaplasty is a safe and effective alternative to mastectomy or standard breast-conserving surgery. Further work is required to explore the impact of the technique on quality of life, and to establish cost-effectiveness. Abstract : Reduces mastectomy rates